2010
DOI: 10.1128/iai.00506-09
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival of Mice Deficient in Secretory Immunoglobulin M following Systemic Infection withCryptococcus neoformans

Abstract: ؉ splenocytes from both mouse strains had fungicidal activity against C. neoformans. Taken together, these results suggest that the inflammatory milieu in sIgM ؊/؊ mice might confer enhanced resistance to systemic cryptococcosis, stemming in part from the antifungal activity of B-1 B cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 83 publications
1
22
0
Order By: Relevance
“…Numerous studies have now shown that B cells play a crucial role in protection against experimental cryptococcosis [131133]. Prior to these reports, very few studies directly examined the role of B cells in host defense against C. neoformans .…”
Section: The Role Of B Cells In Immunity To C Neoformansmentioning
confidence: 99%
“…Numerous studies have now shown that B cells play a crucial role in protection against experimental cryptococcosis [131133]. Prior to these reports, very few studies directly examined the role of B cells in host defense against C. neoformans .…”
Section: The Role Of B Cells In Immunity To C Neoformansmentioning
confidence: 99%
“…Recently, it was shown that mice that lack IgM, sIgM −/− mice, were more resistant to i.p. infection with C. neoformans than IgM-sufficient mice (22). This finding might appear to be at variance with human data showing that levels of GXM-binding IgM are lower in patients at high risk for CD, namely, HIV-infected patients (12, 23-25), than those at low risk, such as solid organ transplant recipients who subsequently developed CD (13).…”
mentioning
confidence: 99%
“…This finding might appear to be at variance with human data showing that levels of GXM-binding IgM are lower in patients at high risk for CD, namely, HIV-infected patients (12, 23-25), than those at low risk, such as solid organ transplant recipients who subsequently developed CD (13). However, given that sIgM −/− mice have an expanded B-1 B cell repertoire (22, 26) and normal levels of IgG2a, which is highly opsonic for C. neoformans , B-1 B cells and/or acquired Ab immunity are likely to protect sIgM −/− mice against i.p. infection (22).…”
mentioning
confidence: 99%
“…To test the hypothesis that the inability of B cells to produce IgM would impair anticryptococcal defense, Subramaniam et al [95] used mice genetically altered to lack serum IgM (sIgM −/− mice, secretory IgM-deficient). Surprisingly, these mice proved relatively resistant to a systemic cryptococcal challenge delivered intraperitoneally; this observation also seemed to run counter to human data, in which a lack of GXM-reactive IgM translated to higher risks of cryptococcal disease [50,52], as well as mouse data by different groups, showing that acquired, GXM-reactive IgM confers protection against intraperitoneal cryptococcal infection [35,55,73].…”
Section: Corroboration From Mouse Studiesmentioning
confidence: 99%
“…The B-1a subset of mouse B cells are homologous to the human IgM + memory B cells with protective abilities against encapsulated pathogens [53,96]; sIgM −/− mice have an expanded B-1a B-cell pool localized predominantly in the peritoneal cavity and spleen. Secondly, naive and C. neoformans-challenged sIgM −/− mice had higher levels, respectively, of total and GXM-specific IgG2a, an IgG subtype with known protective effects against C. neoformans (see discussion of [95]). In contrast, when in a subsequent study with the same sIgM −/− model, Subramaniam et al used an intranasal, pulmonary infection model that delivered the cryptococcal inoculum straight to the lungs, these mice succumbed to the infection at a higher rate relative to the IgM-sufficient controls, with higher fungal burdens in the blood and brain [97]; the alveolar macrophages of sIgM −/− mice appeared deficient in phagocytosis of cryptococcal cells, but regained the function when nonspecific polyclonal IgM was administered to the lungs via the same intranasal route.…”
Section: Corroboration From Mouse Studiesmentioning
confidence: 99%